2020
DOI: 10.1371/journal.pone.0239462
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous polyposis coli-binding protein end-binding 1 promotes hepatocellular carcinoma growth and metastasis

Abstract: This study was performed to determine the clinical significance of adenomatous polyposis coli (APC)-binding protein end-binding 1 (EB1) in hepatocellular carcinoma (HCC) and to characterize its biochemical role in comparison with previous reports. We performed immunohistochemical staining to detect EB1 expression in tissues from 235 patients with HCC and investigated its correlations with clinicopathological features and prognosis. We also investigated the roles of EB1 in cell proliferation, migration, and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Since we profiled the MAPRE1-and STMN1-RNA interactomes in liver cancer cells (HepG2), we inspected the association with hepatocellular carcinoma (LIHC). MAPRE1 and STMN1 have been linked to promote liver cancer progression through mechanisms exerted by the canonical functions in cytoskeletal remodeling (Aiyama et al, 2020;Lu et al, 2018;Orimo et al, 2008;Wong et al, 2008). We found that upregulation of MAPRE1 and STMN1 gene expression correlated with the severity of the pathological stage and significantly decreased patient survival in LIHC patients (Figure 6E-F).…”
Section: Non-canonical Rbps Have Specialized Rna Interactomesmentioning
confidence: 76%
“…Since we profiled the MAPRE1-and STMN1-RNA interactomes in liver cancer cells (HepG2), we inspected the association with hepatocellular carcinoma (LIHC). MAPRE1 and STMN1 have been linked to promote liver cancer progression through mechanisms exerted by the canonical functions in cytoskeletal remodeling (Aiyama et al, 2020;Lu et al, 2018;Orimo et al, 2008;Wong et al, 2008). We found that upregulation of MAPRE1 and STMN1 gene expression correlated with the severity of the pathological stage and significantly decreased patient survival in LIHC patients (Figure 6E-F).…”
Section: Non-canonical Rbps Have Specialized Rna Interactomesmentioning
confidence: 76%
“…Previous studies show that EB1 is required for persistent directional migration [ 33 , 52 ]. Although not addressed directly in this study, EB1 has been reported to be overexpressed in diverse cancer types and to have pro-invasive functions [ 53 , 54 , 55 , 56 ]. Migration and invasion through basal membranes are two distinct sequential steps of the metastatic process.…”
Section: Discussionmentioning
confidence: 99%